EPISTEMOLOGI ILMU ASBAB AL-WURUD HADIS - Lestari, Lenni (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
Apple-interchange-newline"> This paper is supposed to explore the epistemology of sabab al-wurūd of hadith. The fial result are: First, asbāb al-wurūd is defied as a knowledge which pay attention to the causes of the emergence of an hadith and the condition around it. Second, the source of asbāb al-wurūd knowledge are books (read: creation) which related to the knowledge of asbāb al-wurūd. Third, the method to get asbāb al-wurūd is mainly trough narration (riwayat) and effort on judgment (ijtihad). Both last methods are dividedinto two, that are trough the narration of micro asbāb al-wurūd andtrough the effort on judgment of macro asbāb al-wurūd. Every hadith hasmacro asbāb al-wurūd but not every one of it has micro asbāb al-wurūd.Fourth, asbāb al-wurūd, as a knowledge is a science focuses to the studyof matn. Fifth, historically, asbāb al-wurūd didn’t have any contact to thephilosophy of science, but based on truth theory, the one which is moreappropriate to the process of asbāb al-wurūd’s validation is the coherencetruth theory.